A contribution to taxonomy of the superfamily Grylloidea Laicharting from Yunnan, China (Orthoptera: Grylloidea) - Wang, Ping; Zhang, Dong-Xiao; Yuan, Li-Lan; Liu, Hao-Yu (Zootaxa, 2020)
This paper describes four new species of the superfamily Grylloidea from Yunnan, China, including a new species of Gryllidae: Tarbinskiellus sororius Wang, Zhang & Liu sp. nov.; a new species of Mogoplistidae: Ornebius yunnanensis Wang, Zhang & Liu sp. nov.; two new species of Trigonidiidae: Homonemobius curifolis Zhang, Wang & Liu sp. nov. and Pteronemobius (Pteronemobius) truncates Zhang, Wang & Liu sp. nov. In addition, photographs of habitus and genitalia and a distribution map are provided.